Supply Chain Performance Measurement Usng Supply Chain Operation Reference (SCOR) 12.0 Model : A Case Study in A A Leather SME in Indonesia. (December 2019) - Kusrini, E; Caneca, V I; Helia, V N; Miranda, S
Abstract: The leather industry is one of the basic ingredients in fashion and textile/apparel that has good development potential. This can be used to take advantage of the opportunity for the leather industry which is still importing 60-70%. Supply chain measurement is needed to determine production capability and moreover to benchmark for its company, government, and academics. Measurement of supply chain performance is carried out using the newest-SCOR 12.0 method with a performance and processes approach. The study was conducted on XYZ SME and limited to bag product which is one of the largest leather industries in the Bantul area, Special Region of Yogyakarta. The value of supply chain performance is 54.29, which based on performance indicators. This value included in the average category. It can be inferred as the benchmark for the leather industry around areas to improve supply chain performance.